2002
DOI: 10.1093/hmg/11.11.1281
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease is associated with a TNF polymorphism that affects an interaction between the OCT1 and NF-kappaB transcription factors

Abstract: Tumour necrosis factor-alpha (TNF) expression is increased in inflammatory bowel disease (IBD), and TNF maps to the IBD3 susceptibility locus. Transmission disequilibrium and case-control analyses, in two independent Caucasian cohorts, showed a novel association of the TNF(-857C) promoter polymorphism with IBD (overall P=0.001 in 587 IBD families). Further genetic associations of TNF(-857C) with IBD sub-phenotypes were seen for ulcerative colitis and for Crohn's disease, but only in patients not carrying commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
158
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(166 citation statements)
references
References 53 publications
5
158
3
Order By: Relevance
“…Thus, the association between TNF-␣ polymorphisms, its production, and disease has been studied by a number of investigators. While in a number of studies it was concluded that such an association exists (57)(58)(59)(60)(61), other studies did not find evidence for this (62)(63)(64). This is not surprising since factors modulating the cytokine synthesis or molecules mediating its activity such as TNF receptors are also expected to impact TNF-␣-dependent functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the association between TNF-␣ polymorphisms, its production, and disease has been studied by a number of investigators. While in a number of studies it was concluded that such an association exists (57)(58)(59)(60)(61), other studies did not find evidence for this (62)(63)(64). This is not surprising since factors modulating the cytokine synthesis or molecules mediating its activity such as TNF receptors are also expected to impact TNF-␣-dependent functions.…”
Section: Discussionmentioning
confidence: 99%
“…The current model suggests that in the presence of the minor T allele, a novel transcription factor binding site (OCT-1) is generated at the promoter region of the TNFA gene, immediately next to a preexisting NF-B binding site. As a result, an altered regulation of the gene might be generated in response to various stimuli, which involves the activation of NF-B [63]. The protective nature of the -857T allele has also been suggested by reports on the pathogenesis of other chronic inflammatory diseases, suggesting the general importance of this SNP in the regulation of TNFA gene expression [63,64].…”
Section: The Role Of Tnf-␣ In the Predisposition To Acnementioning
confidence: 95%
“…The next 5 years will hopefully extend this work by addressing missing heritability and elucidating the molecular mechanisms underlying innate immunodeficiency. It may be that improved or augmented genetic screening tools will be able to detect risk alleles of lower frequency than those currently described [116], and further study of epistasis (gene-gene interactions [139,140]) may be key to understanding the pathogenesis of complex phenotypes. There is potentially a wealth of knowledge contained within the known IBD loci [121], and fine mapping of the genes within these regions will identify novel genetic influences.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%